Construction of PD risk predicting model and evaluation indices. - Yatan Li (21439415) (2025)
(A) Construction of the nomogram of the PD disease risk prognosis model on the basis of the three biomarkers. (B) ROC curve of the model. (C) The calibration curve evaluating the predictive accuracy of the model. (D) Clinical impact curve evaluating the model’s clinical performance.